2007
DOI: 10.1002/art.23035
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon as a novel risk factor for endothelial progenitor cell depletion and endothelial dysfunction in systemic lupus erythematosus

Abstract: Objective. The premature atherosclerosis seen in patients with systemic lupus erythematosus (SLE) is not explained by traditional risk factors. SLE disease activity, such as renal involvement and presence of autoantibodies, is associated with elevated serum levels of type I interferon (IFN-I), a family of cytokines with potent antiviral and antiproliferative effects. This study was undertaken to test the hypothesis that elevated IFN-I levels could lead to endothelial dysfunction, a surrogate for cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 48 publications
6
158
1
2
Order By: Relevance
“…Our results showed a statistically significant difference in CD146 level between SLE patients and controls with a mean of 4.2±1.1, 2.2±0.7, respectively, and this in agreement with results of Robak et al 14 In contrast to our data, two other reports showed significant deficiency of circulating endothelial cell count in their SLE patients. 15,16 An explanation for these discrepancies may be the fact that our study included Egyptians only, whereas their studies involved Africans, Americans, whites, and others. Our results showed no statistically significant correlation between CD146 and patients age or the disease duration, and this was consistent with findings of Elshal et al 17 and Abdelaziz et al, 18 who demonstrated that CD146 level was independent of the age of SLE patients and/or the duration of the disease.…”
Section: Discussionmentioning
confidence: 86%
“…Our results showed a statistically significant difference in CD146 level between SLE patients and controls with a mean of 4.2±1.1, 2.2±0.7, respectively, and this in agreement with results of Robak et al 14 In contrast to our data, two other reports showed significant deficiency of circulating endothelial cell count in their SLE patients. 15,16 An explanation for these discrepancies may be the fact that our study included Egyptians only, whereas their studies involved Africans, Americans, whites, and others. Our results showed no statistically significant correlation between CD146 and patients age or the disease duration, and this was consistent with findings of Elshal et al 17 and Abdelaziz et al, 18 who demonstrated that CD146 level was independent of the age of SLE patients and/or the duration of the disease.…”
Section: Discussionmentioning
confidence: 86%
“…Although modulation of EPC numbers has been identified in the course of cardiovascular disease or vascular trauma (which appears to be predictive of clinical coronary events in the general population), there is still much controversy regarding their true identity and role. In SLE, while most of the studies demonstrated low percentages of circulating EPC (Lee et al, 2007;Moonen et al, 2007;Westerweel et al, 2007;Robak et al, 2009), results are inconsistent, most likely due to different protocols adopted for identifying EPC (Hooks et al, 1979). Nevertheless, whether the number of circulating EPC can predict cardiovascular events in patients with SLE remains to be answered by prospective studies.…”
Section: Epc In Slementioning
confidence: 99%
“…78 SLE patients with high type I IFN activity in the serum display substantial endothelial dysfunction, which has been proposed as a mechanism of the increased risk for CVD in SLE patients. 79 Type I IFN signaling is upregulated in ruptured human atherosclerotic plaques, and accelerates disease in hypercholesterolemic mice, suggesting a deleterious function of this cytokine in atherosclerotic CVD. 80 Anti-IFNα therapy is under investigation in the "low" type I IFN subgroup of SLE patients, in whom it has been associated with clinical improvements.…”
Section: Induction Of Protective Treg Responsesmentioning
confidence: 99%